(untitled) (Global Journal of Human-Social Science, 2017)
Introduction Human Immunodeficiency Virus Acquired Immunodeficiency Syndrome HIV AIDS has become increasingly public health problem worldwide Particularly in developing countries higher institutions like Ethiopia The victims are youngsters productive age of the population The primary prevention and control of the spread of HIV AIDS infection is through awareness and changing behavior remains at the highest priority However few studies have been conducted among university students of Ethiopia on their self-efficacy of Human Immunodeficiency Virus Acquired Immunodeficiency Syndrome prevention and control Hence this research was intended to investigate the Knowledge and self-efficacy of Madda Walabu University Undergraduate Students on HIV AIDS Methods An institutional-based cross-sectional the study design was conducted among 605 under graduate students of MaddaWalabu University students were selected using random sampling and data were collected using by structured self-administered questionnaire Descriptive independent sample t-test and ANOVA were computed to analyze the data Result This study result shows that among the total study participants majority of the students 81 3 has ever experienced sexual relationship Nearly half 52 4 of the students use condom during sexual intercourse consistently About half 49 37 of them had moderate level of knowledge regarding Human Immunodeficiency Virus Acquired Immunodeficiency Syndrome infection and of which only 28 4 of them had regular sexual partner Students level of knowledge regarding Human Immunodeficiency Virus Acquired Immunodeficiency Syndrome significantly predictor of their level of self-efficacy and condom use R 0 445 and R2 0 198 Conclusion The knowledge students have on human immunodeficiency virus acquired immune deficiency syndrome significantly predicts self-efficacy of protecting oneself from HIV AIDS Most students at the age of adolescence habit sexual intercours